Long head of biceps tendon augmentation in rotator cuff repair enhances tendon healing, shoulder function and patient‐reported outcomes one‐year post‐surgery - Pablo Cañete San Pastor; Inmaculada Prosper Ramos; Alberto Garcia Roig; Joan Andreu Safont (Journal of Experimental Orthopaedics)
Abstract Purpose The aim is to determine the effect on healing and functionality of patients after 1 year of biceps augmentation of a rotator cuff repair (RCR) compared to RCR plus long head of the biceps (LHB) tenotomy. In addition, to analyse the main factors involved in the recovery after the surgery. Methods A prospective, comparative, non‐randomized study (Level of Evidence III) was conducted. Patients with repairable rotator cuff tears were allocated to either the control group, with a double row transosseous equivalent RCR with LHB tenotomy, or the RCR+augmentation with LHB group. Patients were evaluated for radiological (MRI), clinical (cuff size, Patte and Goutallier scales) and functional variables (Constant and American Shoulder and Elbow Surgeons [ASES] scales) before the intervention. At 1‐year follow‐up cuff healing was confirmed through MRI and functional evaluation with Constant, ASES, simple shoulder test [SST] and Disabilities of the Arm, Shoulder and Hand scales. Results Seventy‐seven patients underwent control or RCR+augmentation with LHB, there were no preoperative differences between the groups. After 1 year of the surgery, re‐rupture occurred in 38.5% and 16% of the patients in control and RCR+augmentation with LHB groups, respectively (p = .026). Total functionality was higher (p < .05) in RCR+augmentation with LHB than in the control group: Constant, SST and ASES scales. Among the explored factors involved in healing, re‐rupture occurred in 100% of the cases with high fatty degeneration. Besides, higher initial functionality (Constant scale) and RCR+augmentation with LHB increased the odds of healing (odds ratio [OR] = 1.12 [1.04–1.21]; OR = 5 [1, 61], respectively), while higher cuff length had a detrimental effect (OR = 0.92 [0.85–0.99]). Conclusion RCR+augmentation with LHB achieves a higher healing percentage and a better functional evolution than RCR+LHB tenotomy, 1 year after cuff repair. Fatty degeneration, cuff length and initial functionality are the main factors involved in cuff healing. Level of Evidence Level III randomized controlled trial.